Glass ceramic raw material production method

By melting and crystallizing chromium slag with other materials in a high-temperature furnace, high-strength microcrystalline glass raw materials are produced, solving the problem of low economic value of chromium slag and realizing high-value resource utilization.

CN119263642APending Publication Date: 2025-01-07SHANXI TAIGANG STAINLESS STEEL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411432867.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

In existing technologies, chromium slag has low economic value and is mainly used as roadbed stone and refractory aggregate, lacking high-value utilization methods.

Method used

Chromium slag, waste glass, limestone, soda ash, and fluorite are mixed in proportion, crushed, and then melted in a high-temperature furnace. The mixture is then poured, annealed, and cooled. Subsequently, nucleation and crystallization treatments are carried out in a high-temperature furnace to obtain microcrystalline glass raw materials.

Benefits of technology

This improves the economic value of chromium slag and enables the production of microcrystalline glass raw materials with high bending strength and microhardness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a production method of a glass ceramic raw material, which comprises the following steps: uniformly mixing chromium slag, waste glass, limestone, sodium carbonate and fluorite in proportion, then putting the uniformly mixed raw material into a high-temperature furnace for melting, then pouring the molten raw material into a preheated mold, and annealing and cooling in the high-temperature furnace to obtain base glass. And then putting the base glass into a high-temperature furnace, heating to a certain temperature from room temperature, carrying out nucleation and heat preservation treatment, continuously heating to crystallization temperature, carrying out heat preservation treatment, and then cooling along with the furnace to obtain the glass ceramic raw material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of microcrystalline glass production, and in particular to a method for producing microcrystalline glass raw materials. Background Art

[0002] When producing ferrochrome alloy, corresponding waste slag (hereinafter referred to as "chrome slag") will be produced. The main chemical compositions are SiO2, Al2O3, MgO, FeO and Cr2O3, among which Al2O3, MgO and SiO2 have relatively high contents. There is currently no effective utilization method. It is mainly used for roadbed stones, refractory aggregates, etc. after simple crushing. There is currently no utilization method with high economic value.

[0003] Therefore, whether it is possible to develop a method for utilizing chromium slag with high economic value has practical economic significance.

[0004] The object of the present invention is to provide a method for utilizing chromium slag with high economic value. Summary of the invention

[0005] The purpose of the present invention is to provide a method for producing microcrystalline glass raw materials in view of the above problems.

[0006] The object of the present invention is achieved as follows: A method for producing raw materials for microcrystalline glass, comprising the following steps: Step 1: mixing chromium slag, waste glass, limestone, soda ash and fluorite in proportion, the proportion being 25-35 parts of chromium slag, 45-55 parts of waste glass, 10-20 parts of limestone, 2-12 parts of soda ash and 2-12 parts of fluorite; Step 2: crushing the prepared materials to less than 5 mm and mixing them; Step 3: heating the finely ground and mixed materials to 1550±100°C in a high temperature furnace under an air atmosphere for melting, and Keep warm for 1.5-2.5h; then pour the molten raw material into a preheated mold at 500±50℃, and continue to keep warm at 500±50℃ for 2.5-3h, then cool naturally to obtain basic glass; Step 4: crush the basic glass to a particle size of less than 3mm, heat it to 580-730℃ in a high-temperature furnace, keep warm for 1.5-2h, then continue to heat it to 700-850℃, keep warm for 1.5-2h, and then cool it with the furnace to obtain microcrystalline glass raw material; Step 5: Test the microcrystalline glass raw material.

[0007] The components and mass percentages of chromium slag are: SiO2: 26-32%, MgO: 20-25%, Al2O3: 27-32%, CaO: 4-7%, Cr2O3: 7-12%, Fe2O3: 5-8%.

[0008] The bending strength of the raw material of microcrystalline glass reaches more than 100Mpa, and the microhardness reaches more than 6000Mpa.

[0009] The beneficial effects of the present invention are as follows: chromium slag, waste glass, limestone, soda ash and fluorite are crushed and mixed in proportion, and then the mixed raw materials are placed in a high-temperature furnace for melting, and then the molten raw materials are poured into a preheated mold, and annealed and cooled in a high-temperature furnace to obtain basic glass. Then the basic glass is placed in a high-temperature furnace and heated from room temperature to a certain temperature, subjected to nucleation and heat preservation treatment, and then further heated to a crystallization temperature, and heat-insulated, and then cooled with the furnace to obtain a raw material for microcrystalline glass. The above method can improve the economic utilization value of chromium slag. DETAILED DESCRIPTION

[0010] The present invention provides a method for utilizing chromium slag with high economic value: chromium slag, waste glass, limestone, soda ash and fluorite are mixed in proportion, and then the mixed raw materials are placed in a high-temperature furnace for melting, and then the molten raw materials are poured into a preheated mold, and annealed and cooled in a high-temperature furnace to obtain basic glass. Then the basic glass is placed in a high-temperature furnace and heated from room temperature to a certain temperature, subjected to nucleation and heat preservation treatment, and then continued to be heated to the crystallization temperature, and heat-insulated, and then cooled with the furnace to obtain microcrystalline glass raw materials.

[0011] The method for producing raw materials for microcrystalline glass using chromium slag provided by the present invention comprises the following steps: (1) mixing chromium slag, waste glass, limestone, soda ash and fluorite in a prescribed proportion, wherein the proportion is 25-35 parts of chromium slag, 45-55 parts of waste glass, 10-20 parts of limestone, 2-12 parts of soda ash and 2-12 parts of fluorite.

[0012] (2) Crush the above materials to less than 5 mm and mix them evenly.

[0013] (3) The above-mentioned finely ground materials are heated to 1550°C in a high-temperature furnace under air atmosphere for melting and kept at this temperature for 2 hours; the molten raw materials are then poured into a preheated mold at about 500°C and kept at 500°C for 3 hours, and then naturally cooled to obtain the basic glass.

[0014] (4) The base glass is crushed to less than 3 mm, heated to 580-730°C in a high-temperature furnace, kept at this temperature for 2 hours, then further heated to 700-850°C, kept at this temperature for 2 hours, and then cooled in the furnace to obtain a raw material of microcrystalline glass.

[0015] (5) The raw materials of microcrystalline glass are tested and their bending strength reaches above 100Mpa and the microhardness reaches above 6000Mpa.

[0016] The specific implementation modes of the present invention are described below by way of examples, but the specific implementation modes of the present invention are not limited to the following examples. Example 1

[0017] The chromium slag, waste glass, limestone, soda ash and fluorite are mixed in proportion, and then the mixed raw materials are placed in a high-temperature furnace for melting, and then the molten raw materials are poured into a preheated mold, and annealed and cooled in a high-temperature furnace to obtain basic glass. The basic glass is then placed in a high-temperature furnace and heated from room temperature to a certain temperature, subjected to nucleation and heat preservation treatment, and then continued to be heated to the crystallization temperature, and heat-insulated, and then cooled with the furnace to obtain microcrystalline glass raw materials.

[0018] The method for producing raw materials for microcrystalline glass using chromium slag provided by the present invention comprises the following steps: (1) mixing chromium slag, waste glass, limestone, soda ash and fluorite in a prescribed proportion, wherein the proportion is 25 parts of chromium slag, 46 parts of waste glass, 12 parts of limestone, 3 parts of soda ash and 7 parts of fluorite. The main chemical components of chromium slag, waste glass, limestone, soda ash and fluorite are respectively as shown in the following table.

[0019]

[0020] (2) Mix the above materials and crush them to less than 5 mm.

[0021] (3) The above materials are heated to 1550°C in a high-temperature furnace under air atmosphere to be melted and kept warm for 2 hours; the molten raw materials are then poured into a preheated mold at about 500°C and kept warm at 500°C for 3 hours, and then naturally cooled to obtain the basic glass.

[0022] (4) The base glass is crushed to less than 3 mm, heated to 600°C in a high-temperature furnace, kept at this temperature for 2 h, then further heated to 720°C, kept at this temperature for 2 h, and then cooled in the furnace to obtain a raw material of microcrystalline glass.

[0023] (5) The raw materials of microcrystalline glass were tested and their bending strength reached 105Mpa and the microhardness reached 6050Mpa. Example 2

[0024] In this embodiment, based on the embodiment 1, the nucleation and crystallization temperatures of the base glass in the high temperature furnace are further increased from the original 600°C and 720°C to 620°C and 740°C.

[0025] The method for producing raw materials for microcrystalline glass using chromium slag provided by the present invention comprises the following steps: (1) mixing chromium slag, waste glass, limestone, soda ash and fluorite in a prescribed proportion, wherein the proportion is 25 parts of chromium slag, 46 parts of waste glass, 12 parts of limestone, 3 parts of soda ash and 7 parts of fluorite. The main chemical components of chromium slag, waste glass, limestone, soda ash and fluorite are respectively as shown in the following table.

[0026]

[0027] (2) Mix the above materials and crush them to less than 5 mm.

[0028] (3) The above materials are heated to 1550°C in a high-temperature furnace under air atmosphere to be melted and kept warm for 2 hours; the molten raw materials are then poured into a preheated mold at about 500°C and kept warm at 500°C for 3 hours, and then naturally cooled to obtain the basic glass.

[0029] (4) The base glass is crushed to less than 3 mm, heated to 620°C in a high-temperature furnace, kept at this temperature for 2 h, then further heated to 740°C, kept at this temperature for 2 h, and then cooled in the furnace to obtain a raw material of microcrystalline glass.

[0030] (5) The raw materials of microcrystalline glass were tested and their bending strength reached 110Mpa and the microhardness reached 6100Mpa. Example 3

[0031] In this embodiment, based on the embodiment 2, the nucleation and crystallization temperatures of the base glass in the high temperature furnace are further increased from the original 620°C and 740°C to 640°C and 760°C.

[0032] The method for producing raw materials for microcrystalline glass using chromium slag provided by the present invention comprises the following steps: (1) mixing chromium slag, waste glass, limestone, soda ash and fluorite in a prescribed proportion, wherein the proportion is 25 parts of chromium slag, 46 parts of waste glass, 12 parts of limestone, 3 parts of soda ash and 7 parts of fluorite. The main chemical components of chromium slag, waste glass, limestone, soda ash and fluorite are respectively as shown in the following table.

[0033]

[0034] (2) Mix the above materials and crush them to less than 5 mm.

[0035] (3) The above materials are heated to 1550°C in a high-temperature furnace under air atmosphere to be melted and kept warm for 2 hours; the molten raw materials are then poured into a preheated mold at about 500°C and kept warm at 500°C for 3 hours, and then naturally cooled to obtain the basic glass.

[0036] (4) The base glass is crushed to less than 3 mm, heated to 640°C in a high-temperature furnace, kept at this temperature for 2 h, then further heated to 760°C, kept at this temperature for 2 h, and then cooled in the furnace to obtain a raw material of microcrystalline glass.

[0037] (5) The raw materials of microcrystalline glass were tested and their bending strength reached 114Mpa and the microhardness reached 6140Mpa. Example 4

[0038] In this embodiment, based on the embodiment 3, the nucleation and crystallization temperatures of the base glass in the high temperature furnace are further increased from the original 640°C and 760°C to 660°C and 780°C.

[0039] The method for producing raw materials for microcrystalline glass using chromium slag provided by the present invention comprises the following steps: (1) mixing chromium slag, waste glass, limestone, soda ash and fluorite in a prescribed proportion, wherein the proportion is 25 parts of chromium slag, 46 parts of waste glass, 12 parts of limestone, 3 parts of soda ash and 7 parts of fluorite. The main chemical components of chromium slag, waste glass, limestone, soda ash and fluorite are respectively as shown in the following table.

[0040]

[0041] (2) Mix the above materials and crush them to less than 5 mm.

[0042] (3) The above materials are heated to 1550°C in a high-temperature furnace under air atmosphere to be melted and kept warm for 2 hours; the molten raw materials are then poured into a preheated mold at about 500°C and kept warm at 500°C for 3 hours, and then naturally cooled to obtain the basic glass.

[0043] (4) The base glass is crushed to less than 3 mm, heated to 660°C in a high-temperature furnace, kept at this temperature for 2 h, then heated to 780°C, kept at this temperature for 2 h, and then cooled in the furnace to obtain a raw material of microcrystalline glass.

[0044] (5) The raw materials of microcrystalline glass were tested and found to have a bending strength of 119 MPa and a microhardness of 6180 MPa. Example 5

[0045] In this embodiment, based on the embodiment 4, the nucleation and crystallization temperatures of the base glass in the high temperature furnace are further increased from the original 660°C and 780°C to 680°C and 800°C.

[0046] The method for producing raw materials for microcrystalline glass using chromium slag provided by the present invention comprises the following steps: (1) mixing chromium slag, waste glass, limestone, soda ash and fluorite in a prescribed proportion, wherein the proportion is 25 parts of chromium slag, 46 parts of waste glass, 12 parts of limestone, 3 parts of soda ash and 7 parts of fluorite. The main chemical components of chromium slag, waste glass, limestone, soda ash and fluorite are respectively as shown in the following table.

[0047]

[0048] (2) Mix the above materials and crush them to less than 5 mm.

[0049] (3) The above materials are heated to 1550°C in a high-temperature furnace under air atmosphere to be melted and kept warm for 2 hours; the molten raw materials are then poured into a preheated mold at about 500°C and kept warm at 500°C for 3 hours, and then naturally cooled to obtain the basic glass.

[0050] (4) The base glass is crushed to less than 3 mm, heated to 680°C in a high-temperature furnace, kept at this temperature for 2 h, then further heated to 800°C, kept at this temperature for 2 h, and then cooled in the furnace to obtain a raw material of microcrystalline glass.

[0051] (5) The raw materials of microcrystalline glass were tested and their bending strength reached 123Mpa and the microhardness reached 6210Mpa. Example 6

[0052] In this embodiment, based on the embodiment 5, the nucleation and crystallization temperatures of the base glass in the high temperature furnace are further increased from the original 680°C and 800°C to 700°C and 820°C.

[0053] The method for producing raw materials for microcrystalline glass using chromium slag provided by the present invention comprises the following steps: (1) mixing chromium slag, waste glass, limestone, soda ash and fluorite in a prescribed proportion, wherein the proportion is 25 parts of chromium slag, 46 parts of waste glass, 12 parts of limestone, 3 parts of soda ash and 7 parts of fluorite. The main chemical components of chromium slag, waste glass, limestone, soda ash and fluorite are respectively as shown in the following table.

[0054]

[0055] (2) Mix the above materials and crush them to less than 5 mm.

[0056] (3) The above materials are heated to 1550°C in a high-temperature furnace under air atmosphere to be melted and kept warm for 2 hours; the molten raw materials are then poured into a preheated mold at about 500°C and kept warm at 500°C for 3 hours, and then naturally cooled to obtain the basic glass.

[0057] (4) The base glass is crushed to less than 3 mm, heated to 700°C in a high-temperature furnace, kept at this temperature for 2 h, then further heated to 820°C, kept at this temperature for 2 h, and then cooled in the furnace to obtain a raw material of microcrystalline glass.

[0058] (5) The raw materials of microcrystalline glass were tested and found to have a bending strength of 125 MPa and a microhardness of 6220 MPa. Example 7

[0059] In this embodiment, based on the embodiment 6, the nucleation and crystallization temperatures of the base glass in the high temperature furnace are further increased from the original 700°C and 820°C to 720°C and 840°C.

[0060] The method for producing raw materials for microcrystalline glass using chromium slag provided by the present invention comprises the following steps: (1) mixing chromium slag, waste glass, limestone, soda ash and fluorite in a prescribed proportion, wherein the proportion is 25 parts of chromium slag, 46 parts of waste glass, 12 parts of limestone, 3 parts of soda ash and 7 parts of fluorite. The main chemical components of chromium slag, waste glass, limestone, soda ash and fluorite are respectively as shown in the following table.

[0061]

[0062] (2) Mix the above materials and crush them to less than 5 mm.

[0063] (3) The above materials are heated to 1550°C in a high-temperature furnace under air atmosphere to be melted and kept warm for 2 hours; the molten raw materials are then poured into a preheated mold at about 500°C and kept warm at 500°C for 3 hours, and then naturally cooled to obtain the basic glass.

[0064] (4) The base glass is crushed to less than 3 mm, heated to 720°C in a high-temperature furnace, kept at this temperature for 2 h, then further heated to 840°C, kept at this temperature for 2 h, and then cooled in the furnace to obtain a raw material of microcrystalline glass.

[0065] (5) The raw materials of microcrystalline glass were tested and their bending strength reached 126Mpa and the microhardness reached 6225Mpa.

[0066] The above description is only a specific embodiment of the present invention, but the structural features of the protection scope of the present invention are not limited thereto. Any changes or modifications made by any technician in the field of the present invention are all covered by the patent scope of the present invention.

Claims

1. A method for producing glass-ceramic raw materials, characterized in that: The following steps are involved: Step 1: Mix chromium slag, waste glass, limestone, soda ash and fluorite in proportion, with the proportion being 25-35 parts of chromium slag, 45-55 parts of waste glass, 10-20 parts of limestone, 2-12 parts of soda ash and 2-12 parts of fluorite; Step 2: Crush the prepared materials to less than 5mm and mix them evenly; Step 3: The finely ground and mixed materials are heated to 1550±100°C in a high-temperature furnace under air atmosphere for melting, and kept warm for 1.5-2.5 hours; then the molten raw materials are poured into a preheated mold at 500±50°C, and kept warm at 500±50°C for 2.5-3 hours, and then cooled naturally to obtain the basic glass; Step 4: crush the base glass to a particle size of less than 3 mm, heat it to 580-730°C in a high-temperature furnace, keep it warm for 1.5-2 hours, then continue to heat it to 700-850°C, keep it warm for 1.5-2 hours, and then cool it with the furnace to obtain the raw material of microcrystalline glass; Step 5: Test the glass-ceramic raw materials.

2. The method for producing glass-ceramic raw materials according to claim 1, characterized in that: The components and mass percentages of chromium slag are: SiO2: 26-32%, MgO: 20-25%, Al2O3: 27-32%, CaO: 4-7%, Cr2O3: 7-12%, Fe2O3: 5-8%.

3. The method for producing glass-ceramic raw materials according to claim 1, characterized in that: The bending strength of the raw material of microcrystalline glass reaches more than 100Mpa, and the microhardness reaches more than 6000Mpa.